THE IMPACT OF TOURIST ARRIVALS AND MSME DEVELOPMENT ON VILLAGE ORIGINAL REVENUE (PAD) IN PEMUTERAN VILLAGE - Savitri, Ni Luh Asri; Dewi, Gusti Ayu Ketut Rencana Sari; Kurniawan, Putu Sukma; Wahyuni, Made Arie (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to examine the influence of tourist arrivals and the growth of Micro, Small, and Medium Enterprises (MSMEs) on the Village Original Revenue (PAD) in Pemuteran Village, Buleleng Regency, Bali, during the period from 2022 to 2024. The research employs a quantitative descriptive-correlational approach based on secondary data obtained from village records and tourism statistics. Over the observed period, the number of tourist visits to Pemuteran increased significantly, indicating a growing interest in the village's ecotourism potential. In 2023, there was also a sharp rise in the number of MSMEs, from 34 to 84 units, which remained stable through 2024. Despite this growth, the PAD fluctuated, decreasing in 2023 before slightly increasing again in 2024. Preliminary analysis suggests that tourist arrivals have a positive relationship with PAD, implying that an increase in tourism activities tends to contribute to higher village revenues. However, the rapid increase in MSMEs did not show a proportional impact on PAD, likely due to the fact that many of these enterprises operate informally and are not fully integrated into the village’s official economic and tax systems. This study recommends strengthening the management of local tourism retributions and encouraging the legal registration of MSMEs, which would help ensure that economic activities contribute effectively and sustainably to the village's financial development.